Kajian pembangunan usahawan di sektor perikanan Malaysia - Mohd Shariff, Mohd Noor; Ali, Jamal; A. Rahman, Badruddin (Penerbit Universiti Utara Malaysia, 2007)
This book discusses on the efficiency of fishermen’s association to the entrepreneurial field with special focus on identifying factors that influence their entrepreneurial skills among the members of Board of Directors of Regional Fishermen Association, states’ fishermen association and the National Fishermen Association (NEKMAT). It also analyse the entrepreneurial activities of the fishermen as well as their business opportunities on fishery products that they can venture either locally or internationally.